Land use and housing policy implications on building whole life carbon - Ilmari Talvitie; Ali Amiri; Seppo Junnila; Jussi Vimpari (Environmental Research Letters, 2025)
Ongoing urbanization and development pose complex challenges in addressing climate change and biodiversity loss. This study evaluates the impact of land use and housing policies on building whole life carbon (WLC) emissions, introducing a novel approach that incorporates carbon stock losses from urban land expansion. Using geospatial data and standardized life cycle assessment methodologies, it analyzes residential buildings in Helsinki from 2001 to 2020. These are grouped into four regional housing portfolios (HPs), with 1040 observations, based on construction period and socioeconomic attributes. Findings show a 42% reduction in WLC emissions (from 24 to 14 kgCO _2 e m ^−2 a ^−1 in Vuosaari) during the study period. These reductions are primarily driven by energy system decarbonization and supported by improved building energy performance in new builds. However, embodied carbon remains a hidden challenge, though some progress is seen in one HP where a rise in biogenic construction led to 13% lower embodied emissions and a substantial increase in carbon storage (from 0.1 to 1.3 kgCO _2 e m ^−2 a ^−1 ). Densification efforts have mitigated carbon losses from land use change, yet they remain meaningful (4%–8% of new build emissions). While lower-density areas show greater carbon losses, the overall variation in emissions between densities in relatively small due to factors pertaining to other life cycle stages. Municipalities and developers must account for these carbon losses from new urban development to better reflect urban sustainability. Additionally, the study presents that carbon emissions per floor area offers only a partial view of building sustainability, as the functional unit moderately correlates with emissions per capita. Hence, a wider array of functional units are required in assessing building emissions. Future research could elaborate on such policies by proposing concrete operational plans.